The COVID-19 Pandemic and Housing Markets in Selected European Countries: Lessons Learnt and Policy Implications - Głuszak, Michał; Belniak, Stanisław (Journal of Public Governance, 2021)
Objectives: The impact of the COVID-19 pandemic has serious economic and social consequences – global, regional, and local. The overall goal of the paper is to investigate the dynamics of housing markets in selected European countries during the first phase of the COVID-19 pandemic. Research Design & Methods: We evaluate housing indicators in three European countries: Spain, Italy, and the UK. We explore house prices and other housing market indicators, such as transaction volume or rents. The paper also discusses major policy concerns regarding the effects of COVID-19 on housing welfare and urban transformations. Findings: We found out that the COVID-19 pandemic had a strong impact on housing transaction volume and housing preferences. We observed a transitionary house price decrease in the UK, but no significant effect was detected in Italy and Spain. Implications / Recommendations: Due to concerns related to housing affordability and overwhelming housing costs, housing policy should target vulnerable group of tenants and property owners. Contribution / Value Added: Despite some obvious transmission mechanisms, the effects of the pandemic on the real estate sector have not been investigated comprehensively in the real-estate, housing, or urban literature to date. This paper aims to fill this gap by discussing the consequences of the pandemic on the housing sector in Europe.